CIVIC MEDIA: TOWARDS AN UNDERSTANDING OF ITS RELEVANCE - Gordon, Eric; Mihailidis, Paul (AoIR Selected Papers of Internet Research, 2015)
The term “civic media” emerged within a polarized context in which can be seen the traces of two contradictory assumptions: 1) all media are civic (media define the structures of social interaction) and 2) all media are the antithesis of civic (media detract from the communities and the public institutions that comprise democracy). The founding of a “Center for Future Civic Media” (the “future” has since been dropped), was formulated around these assumptions, in that it captured the inevitability of a civic framework of the media, while simultaneously positioning technology as a possible future intervention to solve civic ills. In 2007, prior to the Twitter Revolution or the Arab Spring and other pro-democracy movements triggered or facilitated by social media, there was little context for imagining these possibilities outside of government services and political campaigns. The term civic media carved out a possibility space, a way of imagining a future of technology that was pro-social and for public benefit. But why does the designation of a civic media matter in 2016? Certainly, the novelty of the civic application of media and the political tensions in which that novelty existed is the justification for naming the phenomenon in 2007. But we would not claim that that novelty persists today. In fact, we believe that the term civic media has very different connotations, but remains important. Unlike in 2007, there is widespread recognition that online spaces hold considerable potential for civic life (NY TIMES citation), and in fact they are central to institutional and political transformations (A Smith, 2010; Aaron Smith, 2009). The possibility space of civic media has become normalized in certain sectors, as the discourse surrounding civic or government technology demonstrates, and reduced to a set of assumptions about the composition of tools. That government offices are routinely developing civic technology departments demonstrates a mainstreaming of the civic potential of digital technologies (Open Plans, 2012). No longer struggling for attention, civic media is now struggling for differentiation; the danger is in the term ossifying to mean very specific things, in its reduction to the instrumental functionality of tools—i.e. digital tools can increase efficiency or scale. The work of civic media now is to combat its success, to identify a space of criticality as well as instrumentality, which reconstructs a possibility space beyond the normalizing value of the term.